2023
DOI: 10.1186/s40659-022-00410-5
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced azoospermia and testicular damage ameliorated by adipose-derived mesenchymal stem cells

Abstract: Background The testes are highly susceptible to the adverse effects of chemotherapy and radiation at all stages of life. Exposure to these threats mainly occurs during cancer treatment and as an occupational hazard in radiation centers. The present study investigated the regenerative ability of adipose-derived mesenchymal stem cells (ADMSCs) against the adverse effects of cisplatin on the structure and function of the testes. Methods New Zealand wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The present study revealed that CIS increases the immunohistochemical expression of spermatogenic cells for Bax and decreases them for PCNA, indicating an increase of apoptosis and a decrease of the proliferation processes of spermatogenic cells, which coincide with others. , The reduced proliferation of spermatogenic cells in the present study may be owing to the CIS causing low testosterone levels, which in turn causes reduction of spermatogenesis; however, the increased apoptosis may be owing to the excess of ROS production and translocation of Bax from the cytoplasm to the perinuclear site …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study revealed that CIS increases the immunohistochemical expression of spermatogenic cells for Bax and decreases them for PCNA, indicating an increase of apoptosis and a decrease of the proliferation processes of spermatogenic cells, which coincide with others. , The reduced proliferation of spermatogenic cells in the present study may be owing to the CIS causing low testosterone levels, which in turn causes reduction of spermatogenesis; however, the increased apoptosis may be owing to the excess of ROS production and translocation of Bax from the cytoplasm to the perinuclear site …”
Section: Discussionsupporting
confidence: 81%
“…In parallel, cisplatin treatment caused a decrease in the level of serum testosterone. Testosterone promotes protein synthesis in all spermatogenic cells, so it plays a significant role in the formation of sperm . Moreover, cisplatin lowered the immune/inflammatory status and stimulated apoptosis and oxidative stress biomarkers .…”
Section: Introductionmentioning
confidence: 99%
“…The process was repeated for 3 successive passages. Once the desired number of cells was achieved, the cells were cryopreserved in liquid nitrogen 34 .…”
Section: Methodsmentioning
confidence: 99%
“…The digestion was stopped by adding a culture medium, and the cell suspension was collected and centrifuged at 1000 rpm for 3 minutes. The supernatant was discarded, and the cell pellet was resuspended in PBS and centrifuged again before being analyzed by flow cytometry [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The animal model of testicular cell damage was established by intraperitoneal injection of a 10mg/kg cisplatin solution. Three days after modeling, the testicular cell damage model + cell therapy group received a tail vein injection of 3*10^6 CM-DiI-labeled ADSCs cells, while the testicular cell damage model + Ex group received a tail vein injection of 100μg of ADSC-Ex The normal control group and the testicular cell damage model group received an equal volume of saline via tail vein injection [13][14][15]. The procedures of Dil labeling were as follow: remove the supernatant from the culture dish and replace it with serumfree basal medium dulbecco's modified eagle medium/nutrient mixture F-12 (DMEM/F12) for cell cultivation.…”
Section: Model Establishmentmentioning
confidence: 99%